Organocatalytic, Chemoselective, and Stereospecific House–Meinwald Rearrangement of Trisubstituted Epoxides - Dressler, Friedemann; Öhler, Victoria; Topp, Christopher; Schreiner, Peter R. (Synlett, 2024)
We present a novel method for the chemoselective House–Meinwald rearrangement of trisubstituted epoxides under mild conditions with the use of simple perfluorinated disulfonimides as Brønsted acid catalysts. We isolated the α-quaternary aldehyde products in yields of 27–97% using catalyst loadings as low as 0.5 mol% on a scale of 1 mmol. In addition, we show the stereospecific rearrangement using an enantioenriched substrate, which makes this method suitable for applications in total synthesis of natural products.
Keywords: aldehyde synthesis; Brønsted acid; disulfonimide (DSI); epoxide; House–Meinwald rearrangement; organocatalysis; quaternary carbon